Manufacture of Electrical Battery in the Laboratory According to the STEM Teaching Model - Xuan Vuong, Bui (VNU Journal of Science: Education Research; Vol 36 No 2, 2020)
STEM is an effective teaching method that helps learners not only acquire scientific knowledge but also develop their practical skills, practical applications in life. This article introduces the design of laboratory lesson based on the STEM model in which the learning activities of first-year students in chemistry pedagogy aimed at manufacturing a simple electrochemical battery system for 3 hours. Firstly, the students used their skills to search and summarize the information about electrochemical batteries. Next is followed by practical activities such as using commercial batteries for making simple battery systems to power the light bulbs. A challenge was given for students to promote their creativity through a competition to create the brightest electrochemical battery. At the end of the session, students self-assessed according to the established questionnaire that help the teachers can check the effectiveness of teaching-learning.